Entrepreneurship Capital: Determinants and Impact on Regional Economic Performance - David B. Audretsch; Max Keilbach (Max Planck Institute of Economics, 2005)
The literature focusing on the geography of entrepreneurship has developed some-thing of a schizophrenic approach. On the one hand is a series of studies, which have tried to identify characteristics specific to particular regions that account for inter-spatial variations in entrepreneurship. On the other hand is a literature that has ex-amined the impact of entrepreneurship on the economic performance of that region. While the emergence of a statistical link between economic performance and entre-preneurial activity is of considerable interest to both scholars and policy makers alike, it considers the amount of entrepreneurial activity specific to a region as an exogenous endowment. Thus, little guidance is provided as to how policy could ac-tually influence economic performance by generating more entrepreneurial activity. The purpose of this paper is explicitly link these two disparate literatures by suggest-ing that entrepreneurial activity is not exogenous, as this second strand of literature implies, but rather, as the earlier studies indicated, shaped by a number of factors specific to the particular location. Moreover, if entrepreneurship capital cannot be assumed to be exogenous, a single equation estimation would lead to biased results. We therefore estimate both equations simultaneously using three stage least square estimation. The empirical evidence suggests that the degree of spatially specific entrepreneur-ship capital is shaped by regional-specific factors reflecting both entrepreneurial op-portunities and the entrepreneurial capabilities. In turn, the extent of entrepreneur-ship capital has a positive impact on regional economic performance.
Older version: http://hdl.handle.net/10419/19982
Keywords: M13; O32; O47; 330; Entrepreneurship; Economic Output; Production Function; Endogeneity Bias; Three Stage Least Squares; Produktionsfunktion; Produktionsfaktor; Entrepreneurship-Ansatz; Unternehmensgründung; Schätzung; Deutschland